STUDY ON TENSILE PROPERTIES OF ALUMINUM ALLOY WELDING JOINT USING DIC METHOD - CAO GuangLong; CHEN Liang; REN MingFa; CHEN JiLe; ZHANG YaHui (Jixie qiangdu)
In order to obtain the properties of 2219 aluminum alloy welding joint, this work uses digital image correlation（DIC） method, then the whole strain history within the welding zone of 2219 aluminum alloy friction stir welded joint subjected to tensile load is obtained, which in turn facilitates a continuous yield strength curve for the welding zone. The elastic-plastic constitutive equation is employed to describe mechanical properties of the welding zone with its parameters determined by the measured strain history. Then, the relationship between the distances from any location to the weld zone center and parameters in the equation can be established by fitting. Finally, a numerical simulation of welding joint subjected to tensile load is conducted using the mechanical properties given by the obtained relationship. The simulation results agree well with the experimental data. Therefore, it is proposed that the mechanical properties of the welding zone in a welding joint can be accurately obtained by analyzing its stress-strain curves measured by DIC method.